2010
DOI: 10.1097/aln.0b013e3181d3e0df
|View full text |Cite
|
Sign up to set email alerts
|

EphrinBs/EphBs Signaling Is Involved in Modulation of Spinal Nociceptive Processing through a Mitogen-activated Protein Kinases-dependent Mechanism

Abstract: These results demonstrated that activation of MAPKs contributed to modulation of spinal nociceptive information related to ephrinBs/EphBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 66 publications
1
50
2
Order By: Relevance
“…We speculate that species differences may account for these differences as we examined pain behaviors in mice and the previous study used rats. Indeed, in other study, the activation of spinal EphB receptors by using another reagent, ephrinB1-Fc, also produced thermal hyperalgesia and mechanical allodynia in mice (Ruan et al, 2010;Yu et al, 2012). Nevertheless, other factors, such as the use of different doses and different nociception tests, also potentially contributed to the discrepancies between our results and those of the previous study.…”
Section: Ephrinb-ephb Signaling and Paincontrasting
confidence: 75%
“…We speculate that species differences may account for these differences as we examined pain behaviors in mice and the previous study used rats. Indeed, in other study, the activation of spinal EphB receptors by using another reagent, ephrinB1-Fc, also produced thermal hyperalgesia and mechanical allodynia in mice (Ruan et al, 2010;Yu et al, 2012). Nevertheless, other factors, such as the use of different doses and different nociception tests, also potentially contributed to the discrepancies between our results and those of the previous study.…”
Section: Ephrinb-ephb Signaling and Paincontrasting
confidence: 75%
“…or i.t. injection of ephrinB1-Fc [33], [34]. Pre- or post-treatment with MEK inhibitor prevented or reversed hyperalgesia induced by i.pl.…”
Section: Resultsmentioning
confidence: 97%
“…Serving as key nociceptive signals in glial cells, MAPKs are activated and address central sensitization under pain states (Ji et al 2009(Ji et al , 2013Ruan et al 2010). Moreover, numerous studies have shown that all three MAPK members are prone to be phosphorylated following the activation of certain GPCRs, especially chemokine receptors (e.g., CX3CR1 and CXCR2) (Gao and Ji 2010).…”
Section: R E T R a C T E Dmentioning
confidence: 99%